Rac1 signaling in the establishment of the fucoid algal body plan - Hable, Whitney E. (Frontiers in Plant Science, 2014)
Fucoid zygotes use environmental vectors, including sunlight, to initiate a growth axis a few hours after fertilization. The first division is then transversely oriented by the growth axis, producing daughter cells of distinct fates. The tip growing rhizoid cell gives rise to the holdfast, anchoring the alga to the intertidal substratum, while the opposite thallus cell mainly generates the photosynthetic and reproductive stipe and fronds. Elaboration of this simple growth axis thus establishes the basic body plan of the adult; and elucidating the mechanisms responsible for formation of the growth axis is paramount to understanding fucoid morphogenesis. Recent studies have culminated in a model whereby sunlight, and perhaps other environmental cues, activate the signaling protein Rac1 at the rhizoid pole. Here it sets in motion nucleation of a patch of actin filaments that in turn, targets ions, proteins and cellular processes to the future growth site. At germination, Rac1 initiates morphogenesis by inducing transformation of the patch of actin filaments to a structure that delivers vesicles to the growing tip, and a few hours later orients the spindle and cytokinetic plate.